Association between polypharmacy and the long-term prescription of hypnotics in Japan: a retrospective cross-sectional study - Komatsu, Munehiro; Takeshima, Masahiro; Yoshizawa, Kazuhisa; Ogasawara, Masaya; Kudo, Mizuki; Miyakoshi, Eru; Itoh, Yu; Shibata, Nana; Ayabe, Naoko; Mishima, Kazuo (Frontiers in Psychiatry, 2024)
IntroductionHypnotic polypharmacy and its long-term prescriptions constitute the inappropriate use of hypnotics. However, the relationship between hypnotic polypharmacy and prolonged prescriptions remains unclear. This study aimed to elucidate the association between hypnotic polypharmacy and the duration of hypnotic prescriptions.MethodsThis retrospective, cross-sectional study utilized a large dataset from the Japan Medical Data Center. The study population included adults who had been prescribed hypnotics between April 2020 and March 2021, with a focus on those receiving hypnotics in March 2021. Hypnotic polypharmacy was defined as the concurrent prescription of two or more hypnotics in March 2021. The duration of hypnotic prescriptions was measured by calculating the number of months between April 2019 and March 2021 during which hypnotics were prescribed. A binary logistic regression analysis was conducted to assess the relationship between hypnotic polypharmacy and long-term hypnotic prescriptions, adjusting for relevant covariates.ResultsWe included 112,256 patients (mean age: 49.5 years, females: 47.1%). Among them, 67.9% received hypnotic monotherapy, and 32.1% received hypnotic polypharmacy. Compared with adults who were prescribed hypnotics for 1 month, the association with polypharmacy was stronger in those who were prescribed hypnotics for ≥4 months as the duration of the prescription increased (adjusted odds ratio [aOR]: 1.15, 95% confidence interval [CI]: 1.04–1.27, p=0.006 for 4–6 months; aOR 1.35, 95% CI 1.23–1.49, p<0.001 for 7–9 months; aOR 1.58, 95% CI 1.43–1.73, p<0.001 for 10–12 months; and aOR 3.24, 95% CI 2.99–3.52 for 13–24 months).ConclusionsThis study demonstrated a significant association between hypnotic polypharmacy and long-term prescriptions of hypnotics. Initiating insomnia treatment with hypnotic monotherapy may reduce the likelihood of long-term prescriptions, and limiting the duration of hypnotic prescriptions could potentially prevent polypharmacy.